The Nash Solution as a von Neumann–Morgenstern Utility Function on Bargaining Games - Anke Gerber (Homo Oeconomicus, 2020)
In this paper we prove that the symmetric Nash solution is a risk neutral von Neumann–Morgenstern utility function on the class of pure bargaining games. Our result corrects an error in Roth (Econometrica 46:587–594, 983, 1978) and generalizes Roth's result to bargaining games with arbitrary status quo.
Keywords: A12; A30; 330; Bargaining games; Nash solution; Risk neutrality